Comparisons of different approaches and incisions of thyroid surgery and selection strategy - Lu, Qiyu; Zhu, Xuemei; Wang, Peisong; Xue, Shuai; Chen, Guang (Frontiers in Endocrinology, 2023)
Up to now, the traditional open thyroid surgery via a low collar incision remains the standard approach for patients undergoing thyroidectomy. But this conventional approach will inevitably leave patients a neck scar and even cause a variety of complications such as paresthesia, hypesthesia, and other uncomfortable sensations .With the progress of techniques, especially in endoscopic surgery, and the increasing desire for the cosmetic and functional outcomes, various new approaches of thyroidectomy have been invented to avoid or decrease the side effects. Some of these alternative approaches have obvious advantages compared with the traditional surgery in some ways, and already have been used widely in the treatment of thyroid disease, but each of them has limitations. This review aims to evaluate and compare the main different approaches of thyroidectomy to help surgeons to make the proper treatment strategy for different individuals.